Paspalum giuliettiae (Poaceae, Panicoideae), a New Grass from 'Campos Rupestres' of the Chapada Diamantina, Bahia, Brazil - Pimenta, Karena M. (2013)
A new grass species from Brazil, Paspalum giuliettiae, is herein described, illustrated, and compared with some congeners. This new species shares inflorescences with subconjugate primary branches and solitary glabrous spikelets with P. pumilum, but it differs in macromorphological characters and in leaf anatomy. Paspalum giuliettiae has been collected in the Chapada Diamantina, which is the northern portion of the Espinhaço Range, in the central region of the State of Bahia, Brazil. This new Paspalum grows in humid or swampy places in the ‘campos rupestres’ vegetation, above 1,000 m, and seems to be endemic to this region.